Employee empowerment in construction: An implementation model for process improvement - Holt, Gary D.; Love, Peter E.D.; Jawahar Nesan, L. (MCB University Press, 2000)
The business environment of construction organisations has undergone significant change over the last 50 years. As a result, construction management has had to respond to issues such as increasing levels of client expectation, globalisation of the construction economy, cut-throat competition, and tight margins, plus the “inherent” obstacles to operating in the sector, such as separation of design and construction, fragmented production methods, adversarial relationships, and a reluctance to innovate and take up information technology. Furthermore, the problems of poor and unstructured training, multi-tiered management systems, and poor communication provide less than optimal conditions for achieving high quality products in good time and to budget. One approach to addressing these issues is through the concept of employee empowerment. This paper presents an overview of the empowerment concept in the context of construction management, highlighting the hurdles, an implementation process, and achievable benefits.